Rapid palatal expansion effects on mandibular transverse dimensions in unilateral posterior crossbite patients: a three-dimensional digital imaging study - Alessandro Ugolini; Tiziana Doldo; Luis T. Huanca Ghislanzoni; Andrea Mapelli; Roberto Giorgetti; Chiarella Sforza (SpringerOpen, 2016)
Abstract Background The purpose of this controlled study was to investigate indirect effects on mandibular arch dimensions, 1 year after rapid palatal expansion (RPE) therapy. Methods Thirty-three patients in mixed dentition (mean age 8.8 years) showing unilateral posterior crossbite and maxillary deficiency were treated with a RPE (Haas type) cemented on the first permanent molars. Treatment protocol consisted of two turns per day until slight overcorrection of the molar transverse relationship occurred. The Haas expander was kept on the teeth as a passive retainer for an average of 6 months. Study models were taken prior (T1) and 15 months on average (T2) after expansion. A control group of 15 untreated subjects with maxillary deficiency (mean age 8.3 years) was also recorded with a 12-month interval. Stone casts were digitized with a 3D scanner (3Shape, DK). Results In the treated group, both mandibular intermolar distance (+1.9 mm) and mandibular molar angulation (+9°) increased. Mandibular incisor angulation showed an increase of 1.9°. There was little effect on intercanine distance and canine angulation. Controls showed a reduction in transverse arch dimension and a decrease in molar and canine angulation values. Conclusions RPE protocol has indirect widening effects on the mandibular incisors and first molars.